2021
DOI: 10.1038/s41598-021-94307-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and visualization of murine coagulation factor VIII-producing cells in vivo

Abstract: Coagulation factors are produced from hepatocytes, whereas production of coagulation factor VIII (FVIII) from primary tissues and cell species is still controversial. Here, we tried to characterize primary FVIII-producing organ and cell species using genetically engineered mice, in which enhanced green fluorescent protein (EGFP) was expressed instead of the F8 gene. EGFP-positive FVIII-producing cells existed only in thin sinusoidal layer of the liver and characterized as CD31high, CD146high, and lymphatic vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Recent studies using genetically engineered mice in which the enhanced green fluorescent protein (EGFP) rather than the F8 gene transcript was expressed under the regulation of the F8 locus showed that from developmental stage E12, liver sinusoidal epithelial cells (LSECs) exhibit varying amounts of EGFP, FVIII-producing LSECs being visible from the early stages of development. According to these authors, FVIII production becomes a feature of LSEC maturation as levels of LSEC EGFP increase with liver development [ 187 ].…”
Section: Clotting Factor Biosynthesismentioning
confidence: 99%
“…Recent studies using genetically engineered mice in which the enhanced green fluorescent protein (EGFP) rather than the F8 gene transcript was expressed under the regulation of the F8 locus showed that from developmental stage E12, liver sinusoidal epithelial cells (LSECs) exhibit varying amounts of EGFP, FVIII-producing LSECs being visible from the early stages of development. According to these authors, FVIII production becomes a feature of LSEC maturation as levels of LSEC EGFP increase with liver development [ 187 ].…”
Section: Clotting Factor Biosynthesismentioning
confidence: 99%
“…Although the FVIII is mainly synthesized in liver sinusoidal endothelial cells (LSECs) under physiological conditions ( Shahani et al, 2014 ; Hayakawa et al, 2021 ), many studies demonstrated that the ectopic expression of FVIII in hepatocytes was efficient and the FVIII deficiency in HA mice and HA patients were rescued ( Bunting et al, 2018 ; Chen et al, 2019 ; Zhang et al, 2019 ). Successful amelioration of hemophilia A has been reported by several groups targeting the liver-expressed mouse Alb locus in vivo using AAV vectors to transfer the transgene into the liver ( Sharma et al, 2015 ; Chen et al, 2019 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, CLEC-2 is expressed at low levels in dendritic cells, neutrophils, and macrophages in mice [5,[7][8][9]. Besides blood cells, CLEC-2 is expressed at low levels in Kupffer cells and sinusoidal endothelial cells in the livers of humans and mice [5,10].…”
Section: C-type Lectin-like Receptor 2 and Platelet Activation Mechan...mentioning
confidence: 99%